Enantioselective Synthesis of the Sex Pheromone of Lichen Moth, Miltochrista calamine, and Its Diastereomer - Yuan, Gucheng; Liu, Jiawei; Yu, Shihang; Wang, Xueyang; Bian, Qinghua; Wang, Min; Zhong, Jiangchun (Synlett, 2021)
The synthesis of a Miltochrista calamine sex pheromone and its diastereomer has been developed. The key steps of the synthetic approach involved Evans’ chiral auxiliaries and the addition of alkyne to aldehyde, which were firstly applied to prepare this sex pheromone and its diastereomer. The synthetic sex pheromone could be used to trap insects and study physiological and ecological questions of the lichen moth.
Keywords: Miltochrista calamine; sex pheromone; asymmetric synthesis; Evans’ chiral auxiliary; alkynylation of aldehyde